Pengembangan e-modul kimia berbasis proyek pada materi larutan elektrolit dan non elektrolit - Sihombing, Indah Sari; Marham Sitorus (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to find out the results of analysis of chemistry teaching materials on electrolyte and non-electrolyte solution materials used in schools according to BSNP standards, develop e-modules on electrolyte and non-electrolyte solution materials according to BSNP eligibility criteria and are project-based, and find out student learning outcomes after given project-based e-modules. The population in this study was all students of class X MIA SMA Negeri 1 Deli Tua, totaling six classes. The sample in this study was class X MIA 5 who studied using project-based chemistry e-modules. The instrument used is an e-module eligibility questionnaire in accordance with BSNP standards, a learning outcomes test of 20 questions which have been tested as valid. This research uses methods and media development (R&D) with the ADDIE model. The ADDIE model has several stages, namely Analysis, Design, Develop, Implementation, and Evaluation. The results of the e-module feasibility analysis show that the teaching materials resulting from the trial are very valid based on BSNP. Where Ho is rejected and Ha is accepted, it can be concluded that the project-based chemistry learning e-module developed is better in improving students' chemistry learning outcomes in electrolyte and non-electrolyte solutions.